Tribschen – początki burzliwej przyjaźni. Nietzsche vs. Wagner - Choczaj, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Tribschen – the Beginning of a Stormy Friendship. Nietzsche vs. Wagner This text is an analysis of a relationship between two outstanding minds of modernist period. The relationship significantly influenced personality and development of the author of The Birth of Tragedy. The main part of the disquisition focuses on Nietzsche’s complex personality which gets revealed not only in his relationship with Wagner but also in his way of thinking and style of writing, which is still a challenge for most readers.